Pelaksanaan Tanggung Jawab Sosial dan Lingkungan Perusahaan (Corporate Social Responsibility) oleh PT. Transco Energi Utama Di Kabupaten Pesisir Selatan - Muhammad Afif Alfianda; Busyra Azheri; Hengki Andora (LPPM Universitas Ekasakti Padang, 2023)
PT. Transco Energi Utama is engaged in palm oil processing. The company was founded in 2018 and is one of the companies under PT. Incasi Raya Group. History of PT. Transco Energi Utama in distributing Corporate Social Responsibility (Corporate Social Responsibility) is not only concerned with the profits received, therefore in terms of distributing CSR PT. Transco Energi Utama wants to realize its social responsibility through careful planning. The research method used is Empirical Juridical, namely an approach based on field research to obtain primary data as the main data. In addition to field research, library research was also carried out to obtain supporting secondary data. The results of the research show that the implementation of Corporate Social Responsibility by PT. Transco Energi Utama in Pesisir Selatan Regency is implemented through the Community Care Program (PPM), with the first distribution carried out in 2019. PT. Incasi Raya Group as the parent company has the authority to decide on approval of the proposed forms of programs and the amount of CSR funds that have been determined by PT. Transco Energi Utama.